In vitro activity of aztreonam–avibactam against metallo-β-lactamase-producing Enterobacteriaceae—A multicenter study in China - Biying Zhang; Zhichen Zhu; Wei Jia; Fen Qu; Bin Huang; Bin Shan; Hua Yu; Yiwei Tang; Liang Chen; Hong Du (International Journal of Infectious Diseases, 2020)
Objectives: To study the molecular epidemiology of clinical metallo-β-lactamase (MBL)-producing Enterobacteriaceae isolates in China and to evaluate the antimicrobial susceptibility of MBL-Enterobacteriaceae isolates to aztreonam–avibactam. Methods: Bacterial speciation was determined using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. PCR was used to screen for common carbapenemase genes. Antimicrobial susceptibility testing of common clinical antibiotics and aztreonam–avibactam was performed using the standard broth microdilution method. Results: A total of 161 MBL-Enterobacteriaceae isolates were included, with Klebsiella pneumoniae (n = 73, 45.4%) and Escherichia coli (n = 53, 32.9%) being the most common species. Among the 161 isolates, blaNDM (n = 151), blaIMP (n = 13), and blaVIM (n = 2) were detected, including five strains (3.1%) co-harboring two MBLs. MBL-Enterobacteriaceae isolates frequently contained two (n = 55, 34.2%) or more (n = 89, 55.3%) additional serine β-lactamase genes (blaKPC, blaCTX-M, blaTEM, or blaSHV). Antimicrobial susceptibility testing showed that 81.4% of isolates (n = 131) were resistant to aztreonam. The rates of resistance to cefazolin, ceftazidime, ceftriaxone, cefotaxime, ampicillin–sulbactam, amoxicillin–clavulanic acid, and piperacillin–tazobactam were all over 90%. The addition of avibactam (4 μg/ml) significantly reduced the minimum inhibitory concentrations (MICs) of the aztreonam-resistant isolates by more than 8-fold (range ≤0.125 to 4 μg/ml), with a MIC50/MIC90 of ≤0.125/1 μg/ml among the 131 isolates. Overall, 96.9% (n = 156) of the total isolates were inhibited at an aztreonam–avibactam concentration of ≤1 μg/ml. Univariate and multivariate logistic regression analysis found that in patients with MBL-Enterobacteriaceae infections, the presence of pre-existing lung disease (adjusted odds ratio 8.267, 95% confidence interval 1.925–28.297; p = 0.004) was associated with a hazard effect on worse disease outcomes. Conclusions: The combined use of aztreonam–avibactam is highly potent against MBL-Enterobacteriaceae and may serve as a new candidate for the treatment of infections caused by MBL-Enterobacteriaceae in China.